2001
DOI: 10.1046/j.1464-410x.2001.02375.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and spectrum of Malassezia yeasts in the area of the prepuce and glans penis

Abstract: Objective To investigate the frequency and spectrum of lipophilic Malassezia yeasts within the area of the glans penis and preputial space in healthy men, most of whom were uncircumcised. Subjects and methods As the glans penis and the prepuce are abundant in sebaceous glands, 130 clinically healthy men were examined for the presence of Malassezia spp. Two impression preparations each were made on modi®ed Dixon (mDixon) and LeemingNotman agar. The media were used with no added cycloheximide to allow the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 23 publications
3
34
1
1
Order By: Relevance
“…Warm, humid environment, hyperhidrosis, application of oily substances, malnutrition, and immunosuppression are some of the factors that increase the predisposition to an infection. Although we know that Malassezia colonize genitalia in nearly half of healthy men, we do not know the colonization frequency in females [ 123 ].…”
Section: Pityriasis Versicolormentioning
confidence: 91%
“…Warm, humid environment, hyperhidrosis, application of oily substances, malnutrition, and immunosuppression are some of the factors that increase the predisposition to an infection. Although we know that Malassezia colonize genitalia in nearly half of healthy men, we do not know the colonization frequency in females [ 123 ].…”
Section: Pityriasis Versicolormentioning
confidence: 91%
“…142 However, it has recently been suggested that the Malassezia yeasts may also play a role in psoriasis of the glans penis. 143 Clinically, the lesions of psoriasis may resemble those of SD; however, the histologic appearance of the lesions is distinct. Biopsy specimens taken from patients with SD show a spongiform appearance, 144 although older lesions may lose this characteristic and begin to resemble psoriasis.…”
Section: Psoriasismentioning
confidence: 99%
“…Six out of seven Scandinavian M. furfur isolates formed Group IV with 35% homology forming a distinct cluster from Groups V and VI (20% homology) that included all Greek and the global selection of strains (Figure 1). The single M. furfur Scandinavian (GS1A) isolate that was grouped together with the Bulgarian isolates in Group I (37% similarity; Figure 1) could represent a transient member (Mayser et al, 2001) of the Malassezia skin flora. Figure 1 Rooted dendogram constructed using unweighted pair-group method with arithmetic averages (UPMGA) analysis of M. furfur microsatellite PCR fingerprints as generated by Bionumerics software.…”
mentioning
confidence: 99%